Cell Line Derived Xenograft Mouse Models Are a Suitable in vivo Model for Studying Tumor Budding in Colorectal Cancer - Georges, Laurent M. C.; De Wever, Olivier; Galván, José A.; Dawson, Heather; Lugli, Alessandro; Demetter, Pieter; Zlobec, Inti (Frontiers in Medicine, 2019)
Tumor budding (TB) is an important prognostic parameter in colorectal cancer (CRC) and associated with metastasis. However, the mechanisms of TB have not been fully elucidated and a major limitation is the absence of in vivo models. Here, we determine the suitability of mouse cell line derived xenografts (CDX) as models of TB in CRC. Pan-cytokeratin (CK)-stained next-generation Tissue Microarrays (ngTMA) of two CDX models (HT-29, n=12 and HCT-8, n=8) and human CRC (n=25 high-grade and low-grade budding tumors, each) were evaluated for TB. Immunohistochemistry for E-cadherin, β-catenin, Ki-67, ZEB1 and TWIST1 was performed. HT-29 and HCT-8 were predominantly high-grade and no/low-grade TB tumors, respectively. TB counts in the tumor center (intratumoral budding, ITB) were significantly higher in HT-29 CDX tumors compared to human CRC (p=0.0099). No difference was found in TB counts at the invasion front (peritumoral budding, PTB; p=0.07). ITB and PTB were strongly correlated (r=0.438 and r=0.62 in CDX and human CRC, respectively). Immunohistochemistry profiles were comparable in CDX and human CRC tissues. TB in the CDX mouse models is phenotypically similar to human CRCs and highlights comparable protein profiles. The HT-29 CDX could be a suitable model for the in vivo assessment of TB.